Low hemoglobin is associated with poor functional outcome after non-traumatic, supratentorial intracerebral hemorrhage - Diedler, Jennifer; Sykora, Marek; Hahn, Philipp; Heerlein, Kristin; Schölzke, Marion Nicola; Kellert, Lars; Bösel, Julian; Poli, Sven; Steiner, Thorsten (Critical care, 2010)
INTRODUCTION: The impact of anemia on functional outcome and mortality in patients suffering from non-traumatic intracerebral hemorrhage (ICH) has not been investigated. Here, we assessed the relationship between hemoglobin (HB) levels and clinical outcome after ICH. - METHODS: One hundred and ninety six patients suffering from supratentorial, non-traumatic ICH were extracted from our local stroke database (June 2004 to June 2006). Clinical and radiologic computed tomography data, HB levels on admission, mean HB values and nadir during hospital stay were recorded. Outcome was assessed at discharge and 3 months using the modified Rankin score (mRS). - RESULTS: Forty six (23.5%) patients achieved a favorable functional outcome (mRS <or= 3) and 150 (76.5%) had poor outcome (mRS 4 - 6) at discharge. Patients with poor functional outcome had a lower mean HB (12.3 versus 13.7 g/dl, P < 0.001) and nadir HB (11.5 versus 13.0 g/dl, P < 0.001). Ten patients (5.1%) received red blood cell (RBC) transfusions. In a multivariate logistic regression model, the mean HB was an independent predictor for poor functional outcome at three months (odds ratio (OR) 0.73, 95% confidence interval (CI) 0.58-0.92, P = 0.007), along with National Institute of Health Stroke Scale (NIHSS) at admission (OR 1.17, 95% CI 1.11 - 1.24, P < 0.001), and age (OR 1.08, 95% CI 1.04 - 1.12, P < 0.001). - CONCLUSIONS: We report an association between low HB and poor outcome in patients with non-traumatic, supratentorial ICH. While a causal relationship could not be proven, previous experimental studies and studies in brain injured patients provide evidence for detrimental effects of anemia on brain metabolism. However, the potential risk of anemia must be balanced against the risk of harm from red blood cell infusion.
Gesehen am 01.03.2024